The Business of Densification Governing Land for Social Sustainability in Housing - Debrunner, Gabriela (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
Affordable housing shortage and social exclusion have become severe socio-political problems across the globe. Increasing numbers of people are suffering from social eviction and displacement due to urban densification, modernization, rising rents, and intense housing commodification. Vulnerable resident groups - such as old-aged or households with children - who often live in older housing stocks planned to be densified or upgraded with higher rents, are being pushed to the margins of the city. A scenario that is highly unsustainable. So far, studies on densification have mainly considered the process as technological, architectural, or design-based problem. However, systematic knowledge on how to implement densification objectives sustainably - regarding economic, environmental, and social aspects - is still lacking. This book tackles this gap by analyzing densification from a governance perspective. Its point of departure is that densification per se does not necessarily lead to sustainable outcomes in terms of social inclusion, cohesion, or community stability. Rather, it politicizes densification by neglecting how the process is planned, implemented, and governed by the actors (e.g., municipal authorities, landowners) involved. The book applies an actors-centered neoinstitutionalist political ecology approach to reveal the specific objectives and strategies of actors involved, as well as the socio-political structures (i.e. rules, laws, and policies) that govern densification. Four Swiss in-depth empirical qualitative case studies (Zürich, Basel, Köniz, and Kloten) illustrate the political and legal conditions for success or failure for (un)sustainable densification implementation. Finally, this book advises stakeholders on more effective, community-oriented, collective, and decommodified forms of governance to respond to the needs of the public at large rather than simply catering to private individuals and firms. Gabriela Debrunner has a PhD in geography with a focus on spatial planning and political urbanism. She works as a postdoc, lecturer, and research associate at the Institute for Spatial and Landscape Development (IRL) at ETH Zurich. In her research, Gabriela Debrunner deals with the overarching question of how the city as a social space works from an urban governance perspective.